PERAN ORANG TUA DALAM PENDIDIKAN AGAMA ISLAM ANAK USIA REMAJA DI DESA PANGGURUAN KECAMATAN SUMBUL KABUPATEN DAIRI - Zulkarnaen Guchi, Sela Simbolon, Ramlan Padang, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
The role of parents towards adolescent children is very important. Parents as the main figures in the family are obliged to guide adolescents so that they are always obedient to religious teachings. Parents are also the first educators for their children, because it is from them that children first receive education. Islamic religious education is a conscious and planned effort. Parents have a role as the most important adolescent personality builder in the family, because the parents' personality will be a mirror for the realization of the next teenager. This study aims to determine the role of parents in Islamic religious education for teenagers in Pangguruan Village, Sumbul District, Dairi Regency and to determine the obstacles and efforts made by parents in fostering religious education for adolescents in Pangguruan Village. This type of research used is qualitative research. Methods of data collection using interviews, observation, documentation and analysis, the analysis used is a qualitative descriptive approach, namely data reduction, data presentation and drawing conclusions. test the validity of the data using triangulation. From the results of the research that the authors conducted, it was found that the role of parents in Islamic religious education for adolescents in Pangguruan Village, Sumbul District, Dairi Regency had been carried out quite well. This is evident from the way parents educate teenagers from small examples such as always reminding them of the obligation to pray, attending recitations and participating in mosque youth organizations and always directing children to carry out Allah SWT's commands and advising children to do good to fellow beings. Actions taken by parents in adolescent education are quite good in fostering their children.